(untitled) ("Journal "U". Economy. Management. Finance.", 2021)
The article discusses the modern features of financial risk management in commercial banks. The characteristics of the key elements of the management mechanism, as well as the principles of management are given. Special attention is paid to the methods due to which the management influence on the financial risks of banking organizations is ensured.